Recovery and use of water from the vinasse biodigestion in industrial processe - Mattos, Eduardo de Castro; Sunhiga Filho, Ricardo Fleury; Calegari, Rubens Perez; Baptista, Antonio Sampaio (Revista Hipótese, 2019)
It was evaluated the physico-chemical treatment of biodigested vinasse and possible reuse in the productive chain of sugarcane. 2 treatments were performed: Filtration followed by flocculation (T1) and centrifugation followed by filtration and flocculation (T2). Turbidity, electrical conducity and pH were evaluated. T1 removed 88.3% of the turbidity and T2 removed 93.4%. There was no change in electrical conductivity. T2 was more efficient, generating a product with low turbidity and possible reuse in industry.
Keywords: Flocculation; Centrifugation; Physical chemical treatment of efluente; Turbidity remotion